Pengaruh Promosi dan Harga terhadap Penjualan pada CV Bandar Sinergi Utama Kota Tangerang - Ridwan Maulana; Herayati Herayati; Vicky Windasari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this research is to determine promotions and prices for sales at CV Bandar Sinergi Utama, both partially and simultaneously. This research is associative with a quantitative approach. Sampling was taken using the Slovin technique. The sample used in this research was 38 respondents. Data collection techniques used questionnaires, data analysis techniques using validity, reliability, hypothesis testing, t tests and f tests with SPSS version 21 software. The research results showed that: (1) Promotion has an effect on sales with a coefficient of determination value of 0.594 which has a significant effect on sales with the result tcount > ttable or (7.250 > 2.030) with a significance value<0.050 or (0.00 < 0.05). (2) There is an influence of price on sales with a coefficient of determination of 0.658 with the result tcount > ttable or ((8.319 >2.030) with a significance value <0.05 or (0.00 <0.05). (3) promotion and price has an effect on sales with the regression equation Y = -0.055 + 0.250 X1 + 0.522 < 0.05) then in this study Ha is acceptable.